2013
DOI: 10.1098/rsta.2011.0634
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the paramagnet-enhanced NMR relaxation of H2encapsulated in endofullerene nitroxides by density-functional theory calculations

Abstract: One contribution of 13 to a Theo Murphy Meeting Issue 'Nanolaboratories: physics and chemistry of small-molecule endofullerenes' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
(74 reference statements)
3
7
0
Order By: Relevance
“…As mentioned above, this approach is questionable for H 2 @C 60 . Nevertheless, in a related work in this Theo Murphy Meeting Issue [42], we have demonstrated that, at least at room temperature, the error involved in treating the motion of H 2 classically is negligible. A final issue concerns the open-shell nature of the species.…”
Section: Density Functional Theory Calculations Of the Hyperfine Intementioning
confidence: 99%
“…As mentioned above, this approach is questionable for H 2 @C 60 . Nevertheless, in a related work in this Theo Murphy Meeting Issue [42], we have demonstrated that, at least at room temperature, the error involved in treating the motion of H 2 classically is negligible. A final issue concerns the open-shell nature of the species.…”
Section: Density Functional Theory Calculations Of the Hyperfine Intementioning
confidence: 99%
“…We previously assumed that τ c is only slightly affected by the C 60 functionalization , an assumption that is supported by DFT calculations . Here, as explained below, we consider that the impact of the peptide‐TOAC moiety on τ c is also negligible.…”
Section: Resultsmentioning
confidence: 77%
“…(1) is negligible. As values of τ c for the fullerene nitroxides are longer than 10 −11 s , 1/ T 1,p should therefore be approximately proportional to τ c . .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of unpaired electrons on the nuclear relaxation of endohedral H 2 in solution is investigated by Rastrelli et al [17]. DFT calculations are conducted on endofullerenes with attached nitroxide moieties.…”
mentioning
confidence: 99%